HUBUNGAN STATUS GIZI DAN KETERSEDIAAN VENTILASI RUMAH DENGAN KEJADIAN ISPA PADA ANAK 1-5 TAHUN - Mukhlis; Muhammad Firmansyah (Rena Cipta Mandiri, 2025)
Acute Respiratory Tract Infection or ISPA is an acute infection that attacks one or more parts of the respiratory tract starting from the nose to the alveoli, ISPA is one of the most common diseases suffered by children and toddlers. The purpose of this study was to determine the relationship between nutritional status and the availability of home ventilation with the incidence of ISPA in children aged 1-5 years. The design used in the study was descriptive analytic with a cross-sectional approach, namely a research approach that was carried out simulatively or carried out at the same time then processed and analyzed with the Sample taken in this study amounted to 51 samples, the sampling technique used was purposive sampling. The instrument used was an observation sheet regarding the relationship between nutritional status and the availability of home ventilation with the incidence of ISPA in children. The results of the study showed a relationship between nutritional status and the availability of home ventilation and the incidence of acute respiratory infections (ARI) in children aged 1-5 years. The criteria were 7 (13.7%), 24 (47.1%) undernourished, 15 (29.4%), and 5 (9.8%) overnourished. Furthermore, 17 (33.3%) had suboptimal ventilation and 34 (66.7%) had ideal ventilation.